Analisis Hukum Mengenai Pertanggungjawaban Korporasi Dalam Kasus Tindak Pidana Oleh PT Asuransi Jiwasraya - Arya Jayadiningrat; Boris William Octaviano; Nyulistiowati Suryanti; Deviana Yuanitasari (Jaksa : Jurnal Kajian Ilmu Hukum dan Politik, 2024)
The term "corporation" is defined broadly in positive criminal law, beyond the limits of the conception of legal entities in civil law. This interpretation includes organized entities involving persons and/or assets, whether or not they have the status of legal entities. Corporate crime has not been explicitly regulated in the Indonesian Criminal Code which refers to the Continental European legal system. The main focus of Continental European criminal law is more inclined to individual responsibility than corporate entities. In contrast, in the Anglo-Saxon legal system, corporate liability in criminal cases is explicitly discussed. However, changes in Indonesian legal views show a shift, directing criminal responsibility to the corporation itself. Nonetheless, criminal law in Indonesia previously tended to direct prosecution towards individuals involved in the management of the corporation. The implementation of corporate liability in corruption cases is still limited, but steps were taken by issuing Supreme Court Regulation No. 13 of 2016 concerning Procedures for Handling Criminal Cases by Corporations (PERMA Korporasi). In this PERMA, the identification of individuals involved in corporate crime is expanded, including those who have a relationship with the company even though they are not formally incorporated into the company structure. The PERMA Corporations approach emphasizes that corporate responsibility only applies if it is proven to be directly involved in the criminal act and benefit from the act. The use of the Business Judgment Rule principle and consideration of the benefits to the corporation are key in assessing corporate guilt. Research on PT Asuransi Jiwasraya highlighted violations committed by management in investment management that harmed the company. These violations include non-compliance with the precautionary principle in investment management, resulting in significant financial losses. Violations of the principles of Corporate Governance were also highlighted in this case.